Empfehlungen der S2e-Leitlinie der Deutschen Gesellschaft für Luft- und Raumfahrtmedizin zu Herz-Kreislauf-Stillstand und kardiopulmonaler Reanimation während Linienflügen - Hinkelbein, Jochen; Adler, C.; Bernhard, M.; Hohn, A.; Jansen, S.; Komorwoski, M.; Neuhaus, Christopher; Warnecke, T. (Notfall & Rettungsmedizin, 2017)
BackgroundIn 2017, more than 3 billion people worldwide will travel by aircraft and commercial air transport. Although air travel is safe, between 1 out of 14,000 to 1 out of 50,000 passengers will experience acute medical problems (in-flight medical emergencies, IFME) during their flight. Cardiac arrest during air travel accounts for 0.3% of all IFME, but it is the cause of 86% in-flight deaths.Methods and resultsBy using a systematic literature search including the GRADE, RAND, and DELPHI methods, 28 specific recommendations on this topic have been created. Where evidence was lacking, an expert consensus was built. The main recommendations in the guideline are: emergency equipment location as well as content should be mentioned in the preflight safety announcement; it is very important to request help by an on-board announcement after identification of a patient with cardiac arrest; two-person CPR is considered optimum and should be performed if possible; the crew should be trained regularly in basic life support—ideally with a focus on CPR in aircraft; a diversion should immediately be performed if the patient has a return of spontaneous circulation.